Dual routes toward observation of a trans-H2/hydride complex in an iridium pincer system and hydrogenation catalytic activity - Agrawal, Nisha K.; Dash, Soumya R.; Vanka, Kumar; Jagirdar, Balaji R. (Organometallics, 2023)
The Abstraction of chloride from a six- coordinate complex, trans-[ Ir(H)(Cl)((iPr)4)(POCOP)(PPh3)] (1) [((iPr)4)(POCOP) = 2,6-bis(di-iso-propylphosphinito)benzene,kappa(3)-C6H3-1,3-[OP(Pr-i)(2 )](2)], using NaBAr4f leads to the generation of a dinitrogen complex, trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)][BAr4f] (6). Addition of H-2 to [Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)](+) (6) under extremely mild conditions (1 bar, 298 K) resulted in the reversible coordination of H-2 to generate the cis-[Ir(H)(eta H-2-(2))((iPr)4)(POCOP)(PPh3)](+) (cis-11) complex. The cis-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) complex (cis-11) isomerized to a trans isomer, trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) (trans-11), at 253 K. The isomerization process has been studied and supported by computations. Employing an alternative route, protonation of the trans-[Ir(H)(2)((iPr)4)(POCOP)(PPh3)] complex (2) at 183 K resulted in the formation of an identical, trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) complex (trans-11); upon warming the sample, the trans-H-2/hydride complex isomerized to the cis isomer above 253 K. Two independent routes to obtain trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) (trans-11) species have been established. Reaction of trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)][BAr4f] (6) with C2H4 gave the cis-[Ir(H)(eta(2)-C2H4)((iPr)4)(POCOP)(PPh3)](+) complex (cis-15), which also undergoes isomerization to yield an equilibrium mixture of cis/trans-[Ir(H)(eta(2)-C2H4)((iPr)4)(POCOP)(PPh3)](+) complexes (cis-15 and trans-15) at 253 K. The trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)](+) complex (6) is an excellent catalyst for hydrogenation of ethylene to ethane under very mild conditions.

Designing of imine thiophene-ligated metal-complexes and implication in ethylene polymerization - Shaikh, Maulali H.; Ramekar, V. Rohan; Jawoor, Shailaja; Dash, Soumya R.; Birajadar, Rajkumar S.; Pawal, Sandip B.; Thenmani, Nandakumar; Vanka, Kumar; Chikkali, Samir H. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2024)
Polyethylene is the single largest volume polymer produced globally using Ziegler-type catalysts. Numerous modifications have been reported in search of a better catalyst that can control molecular weight, polydispersity, and branching. In our attempts to identify a suitable imine thiophene-ligated chromium complex, we examined 9 different titanium complexes computationally. The DFT investigations considered barriers for insertion, propagation, and termination by beta-H elimination or chain transfer, and identified N-(4-methoxyphenyl)-2-phenyl-1-(thiophen-2-yl)ethan-1-imine(L9) as the most suitable ligand. Subsequently, L9 was prepared in good yield (70%) by condensing 2-phenyl-1-(thiophen-2-yl)ethan-1-one with 4-methoxyaniline. Ligand L9 was treated with early transition metal precursors (Ti, Cr, Zr) to generate a homogenous catalyst. The identity of these catalysts was unambiguously ascertained using a combination of NMR, ICP, FT-IR, UV-Vis spectroscopy, and ESI-MS. The performance of L9-ligated titanium complex [Cat.1] was examined in ethylene polymerization using MMAO as a co-catalyst. Insertion of ethylene was tracked using high-pressure NMR experiments and Cat.1 was found to be active in the polymerization. Ethylene polymerization conditions were optimized to obtain high activity and molecular weight polyethylene. The chromium complex [Cat.2] outperformed the Ti and Zr-derived catalysts with the highest TOF of 6294 mol of PE/mol of Cr/h. Cat.2 produced high molecular weight, high-density polyethylene.
Keywords: Cr-complexes; DFT; high-density polyethylene; Imine thiophene ligand; Polyethylene